Elementos antimodernos na obra de J.R.R.Tolkien: uma análise da obra Sobre Contos de Fadas - SILVA NETO, Jaffi Carvalho da (2024)
The purpose of this paper is to analyze the anti-modern discourse in J.R.R. Tolkien's literature. According to the Catholic discourse at the turn of the 19th to the 20th century, there was a constant institutional disagreement between the Church and Modernity and its defenders, which meant that the Holy See's position towards the new times took on tones of criticism and rejection, as well as a defense of the Christian faith against the so-called moderns. Likewise, there was a vast romantic tradition in Europe, especially in England, which raised flags against capitalism and the market society. In this way, we seek to analyze the essay Tree and Leaf (1945) as a discursive form of the conception of a Catholic ethic, understanding that for this purpose the author (1) relied on Catholic tradition and ideology to conceive his theories on fairy tales and (2) used the support of the romantic tradition as a way of demonstrating the bankruptcy of relationships arising from industrial society. To this end, our work is based on the non-linearity of time and its stratification, according to the thinking of Reinhart Koselleck, on the analysis of the rejection of metaphysics in modernity proposed by Urbano Zilles, on the conceptualization of romanticism and its totality based on the concept of Michael Löwy and on the texts of J.R.R. Tolkien, especially The Letters of J.R.R. Tolkien and the essay On Fairy stories.